BRONKOPNÖMOLOJİ BÖLÜMÜ’NDE PASİF VAKA BULMA YÖNTEMİ İLE SAPTANAN TÜBERKÜLOZLU HASTALARIN RETROSPEKTİF DAĞILIMI - YANARDAĞ, HaliI; BİLİR, Muammer and SiPAHi, Sevtap and MİDİLLİ, Kenan and DEMİRCİ, Sabriye and KARAYEL, Tuncer (Cerrahpaşa Medical Journal, 2014)
Background and Design. Three major methods are used for finding of tuberculosis (TB) cases in a population; finding of symptomatic cases (passive surveillance), active surveillance and screening of high risk populations. In passive surveillance; symptomatic patients attending by themselves to any health care institution or physician, are evaluated with regard of TB: The advantage of this method of the active screening based on microfilm, tuberculin test and sputum examination relies on higher rates of finding both of pulmonary and extrapulmonary TB cases. Patients referred to our outpatient clinic were analysed retrospectively. Results. The rate of case finding in previous active surveillance programs performed between 19601983 in Turkey was 0.76% whereas the corresponding figure in our study was 5.81 % (7.64 fold). The yield of active surveillance programs is very low, compared to the required enormous labour, staff and other resources. On the other hand, passive surveillance is more cost effective, permits identification of extrapulmonary TB cases and is psychologically more comfortable due to voluntary attendance. Conclusion. Regarding all of these we recommend to incorporate the passive surveillance into national TB prevention programs.